Endogenous FGF21-signaling controls paradoxical obesity resistance of UCP1-deficient mice - Keipert, Susanne; Lutter, Dominik; Schroeder, Bjoern O; Brandt, Daniel; Ståhlman, Marcus; Schwarzmayr, Thomas; Graf, Elisabeth; Fuchs, Helmut; de Angelis, Martin Hrabe; Tschöp, Matthias H; Rozman, Jan; Jastroch, Martin (Nature communications, 2020)
Uncoupling protein 1 (UCP1) executes thermogenesis in brown adipose tissue, which is a major focus of human obesity research. Although the UCP1-knockout (UCP1 KO) mouse represents the most frequently applied animal model to judge the anti-obesity effects of UCP1, the assessment is confounded by unknown anti-obesity factors causing paradoxical obesity resistance below thermoneutral temperatures. Here we identify the enigmatic factor as endogenous FGF21, which is primarily mediating obesity resistance. The generation of UCP1/FGF21 double-knockout mice (dKO) fully reverses obesity resistance. Within mild differences in energy metabolism, urine metabolomics uncover increased secretion of acyl-carnitines in UCP1 KOs, suggesting metabolic reprogramming. Strikingly, transcriptomics of metabolically important organs reveal enhanced lipid and oxidative metabolism in specifically white adipose tissue that is fully reversed in dKO mice. Collectively, this study characterizes the effects of endogenous FGF21 that acts as master regulator to protect from diet-induced obesity in the absence of UCP1.
Keywords: bílá tuková tkáň; lidé; Mice, Knockout; Obesity; Energy Metabolism; Signal Transduction; energetický metabolismus; myši; Humans; Uncoupling Protein 1; Adipose Tissue, White; Mice; obezita; signální transdukce; fibroblastové růstové faktory; uncoupling protein 1; Adipose Tissue, Brown; mužské pohlaví; Fibroblast Growth Factors; zvířata; Mice, Inbred C57BL; Animals; myši knockoutované; Male; hnědá tuková tkáň; myši inbrední C57BL